Sifat Fisik Sediaan Masker Gel Peel-Off Ekstrak Kulit Mentimun (Cucumis sativus. L) - Ari Wahyudi; Yuli Nurullaili Efendi; Titi Nurul Hidayah (Universitas Hamzanwadi, 2025)
Cucumber peel (Cucumis sativus L.), often considered an agricultural waste, contains significant levels of flavonoids with antioxidant properties that can prevent premature skin aging. This study aimed to formulate and evaluate the physical properties of peel-off gel masks made from cucumber peel extract in three different concentrations: F1 (0.5%), F2 (1%), and F3 (1.5%). This study was conducted experimentally. The extracts were obtained through maceration using 96% ethanol and incorporated into the Peel-Off mask formulations. The physical quality of the mask formulations was assessed through organoleptic evaluation, homogeneity, spreadability, adhesion, pH, and drying time tests. The results showed that all formulations met the desired criteria. All three formulations showed consistent color, aroma, and viscosity for up to four weeks. The homogeneity test ensured uniform distribution of ingredients without visible lumps. Spreadability values ​​ranged from 5.2 to 5.3 cm, within the optimal range of 5–7 cm. The pH value of all formulations was 6, which is within the safe range for skin application. Adhesion tests showed increased adhesion time with higher extract concentrations, ranging from 15.3 to 17.3 seconds. Drying times for all formulas were within the acceptable range of 15–30 minutes. In conclusion, the peel-off gel masks formulated with cucumber peel extract exhibited suitable physical characteristics and potential for practical cosmetic use, with F3 offering slightly superior performance in some parameters.